Short Naphthalene Organophosphonate Linkers to Microporous Frameworks - Bulut, Aysun; Zorlu, Yunus; Worle, Michael; Cetinkaya, Ahmet; Kurt, Huseyin; Tam, Benjamin; Yazaydin, A. Ozgur; Beckmann, Jens; Yuecesan, Guendog (WILEY-V C H VERLAG GMBH, 2017)
We report two novel 3D porous metal-organophosphonate metal organic frameworks (MOFs) [{Cu(4,4'-bpy)(0.5)(1,4-NDPA-H-2)] (1), [{Cu-2(4,4'-bpy)(0.5)}(1,4-NDPA)] (2) and a non-porous [{Cu(4,4'-bpy)}(2,6-NDPA-H-2)] (3) constructed using the structurally rigid 1,4-naphthalenediphosphonic acid (1,4-NDPA-H-4) and 2,6-naphthalenediphosphonic acid (2,6-NDPA-H-4). 1 and 2 exhibit high surface areas obtained using the structurally rigid and short aromatic organophosphonate linkers with copper. The compound 1 has been further analyzed by TGA and Quantum Design PPMS vibrating sample magnetometer.
Keywords: Ligand Synthesis; Magnetism; Metal Organic Frameworks; Porous Solids; Synthesis by Design; METAL-ORGANIC FRAMEWORKS; COORDINATION POLYMERS; HYDROGEN STORAGE; ION-EXCHANGE; PHOSPHONATE; DESIGN; MOFS; DIPHOSPHONATES; ADSORPTION; CHEMISTRY